Zespół akt dekanatu szadkowskiego w zasobie Archiwum Diecezjalnego we Włocławku. Część II - Szkutnik, Piotr (Biuletyn Szadkowski, 2011)
This is the second part of a description of Szadek Decanate historical documents which are held in the Diocese Record Office in Włocławek. The main focus of this paper has been on the contents of the documents and their place of origin. The preserved archives mainly contain legal regulations; there are much fewer documents relating to Szadek Decanate. On the basis of the 19th century register, it can be estimated that the file in its present form contains only about 10% of the documents once existing.